Importance of halal certifications among Muslim consumers in Davao City a conjoint analysis approach - Abpi, Muhammad Monjid D. (School of Management, University of the Philippines Mindanao, 2016)
Halal certification has been established in the Philippines. He demand on halal food products for Muslims consumers is increasing over the years since the producers and manufacturers are investing and applying halal laws and procedures. However, not all process food products are being certified and if they were certified, several kinds of halal certification exist. There are many certifying bodies established in the Philippines and Muslim consumers are often confused with the different halal certifications that they see in processed food markets. Aside from Halal certifications, other certifications such as Good Manufacturing Practice (GMP) and Hazard Analysis Critical Control Point (HACCP) also proliferate in processed foods. As such, this study was conducted to assess the relative importance of halal certifications to Muslim consumers in Davao City when purchasing process products. A conjoint analysis of corned beef attributes including ?certification? was done to analyze the purchase preference among 398 Muslim consumers in Davao City. The attributes examined were price, packaging, brand and certification. The consumer awareness, perception, and concerns on corned beef and halal certification process were also analyzed. Results showed that certification has the highest relative importance (65.56%) in terms of purchase decision, preferably IDCP certification. The other attributes in order of decreasing relative importance were brand (15.33%), packaging (12.05%), and price (7.07%). The ideal product attribute combination for corned beef is IDCP, Argentina, canned, and PhP 25.00. Clustering was not possible as consumer preferences were observed to be homogenous. When consumers decide to purchase corned beef, their purchase decisions are highly influenced by product certification. This implies that a greater effort must be geared towards educating processed food companies about the value of acquiring Halal certifications and which among the different halal certification should be obtained.